The development of two field‐ready reverse transcription loop‐mediated isothermal amplification assays for the rapid detection of Seneca Valley virus 1. Issue 1 (15th November 2018) - Armson, Bryony; Walsh, Charlotte; Morant, Nick; Fowler, Veronica L.; Knowles, Nick J.; Clark, Duncan
Abstract: Seneca Valley virus 1 (SVV‐1) has been associated with vesicular disease in swine, with clinical signs indistinguishable from those of other notifiable vesicular diseases such as foot‐and‐mouth disease. Rapid and accurate detection of SVV‐1 is central to confirm the disease causing agent, and to initiate the implementation of control processes. The development of rapid, cost‐effective diagnostic assays that can be used at the point of sample collection has been identified as a gap in preparedness for the control of SVV‐1. This study describes the development and bench validation of two reverse transcription loop‐mediated amplification (RT‐LAMP) assays targeting the 5′‐untranslated region (5′‐UTR) and the VP3‐1 region for the detection of SVV‐1 that may be performed at the point of sample collection. Both assays were able to demonstrate amplification of all neat samples diluted 1/100 in negative pig epithelium tissue suspension within 8 min, when RNA was extracted prior to the RT‐LAMP assay, and no amplification was observed for the other viruses tested. Simple sample preparation methods using lyophilized reagents were investigated, to negate the requirement for RNA extraction. Only a small delay in the time to amplification was observed for these lyophilized reagents, with a time from sample receipt to amplification achieved within 12 min. Although diagnostic validation is recommended, these RT‐LAMP assays are highly sensitive and specific, with the potential to be a useful tool in the rapid diagnosis of SVV‐1 in the field.